Retirement, pensions, and ageing - Ben J. Heijdra; Ward E. Romp (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the effects of demographic shocks and changes in the pension system on the macroeconomic performance of an advanced small open economy. An overlapping-generations model is constructed which includes a realistic description of the mortality process. Individual agents choose their optimal retirement age, taking into account the time- and age profiles of wages, taxes, and the public pension system. The early retirement provision in most pension systems acts as a trap, inducing most workers to retire well before the normal retirement age. Simulations show that pension reform must be drastic for it to have any effects on the retirement behaviour of workers.
Keywords: E10; J26; H55; D91; F41; J11; 330; Altersgrenze; Arbeitsangebot; Overlapping Generations; Alternde Bevölkerung; Makroökonomischer Einfluss; Kleines-offenes-Land; Theorie